The lecturer's guide to quality and standards in colleges and universities (1995)
My aim in this book is to provide a basic handbook for lecturers concerned with quality and standards in the post-compulsory education sector with an emphasis on an entrepreneurial climate, but at the same time retaining a clear educational philosophy. This philosophy is based on the model of the lecturer as a reflective practitioner. Reflective in this sense is more than 'thinking about', it also includes collecting data about practice and analysing it in the light of the social, moral and political context.